WORKING DRAFTS OF LAND MANAGEMENT AS A COMPONENT OF THE INSTITUTIONAL ENVIRONMENT IN THE AREA OF PROTECTION OF LANDS - Stetsyuk, M. P. (Land Management, Cadastre and Land Monitoring, 2013)
It is proved that in the system of institutional environment in relation to the imple‐ mentation of measures for protection and restoration of  land productivity at this stage of development of the market system of  land tenure in Ukraine the  weakest link is working spatial design and financing and stimulation of its activities.